“Acadêmica porque militante e vice-versa”: recortes sobre a trajetória profissional e intelectual de Jane Beltrão (1970-2024) - SILVA, Karoliny da (2025)
This Course Conclusion Paper (TCC) presents an analysis of the professional and intellectual trajectory of Jane Felipe Beltrão, a prominent Brazilian anthropologist, who contributed to the fields of legal anthropology, indigenous ethnology, gender studies and human rights. The study partially investigates how his academic and militant activities influenced public policies and social movements, focusing on the defense of indigenous peoples and marginalized populations. By examining his career, the work maps the milestones of his academic production and evaluates the impact of his research on strengthening debates about gender, ethnicity and human rights in Brazil. The study is based on the hypothesis that Jane Felipe Beltrão consolidated the intersection between science and activism, overcoming institutional barriers and promoting changes both in the academic environment and in the social and political context. The qualitative methodology is based on bibliographic and documentary research, examining publications, interviews and participation in academic events in Beltrão. The work also analyzes the impact of his research on the formulation of public policies and social movement strategies. With this study, we seek to contribute to the understanding of Jane Felipe Beltrão legacy in Brazilian anthropology and the fight for human rights, with an emphasis on valuing indigenous cultures and defending oppressed populations.